March (2013), book two - Lewis, John. (San Diego : Top Shelf Productions, 2017)
After the success of the Nashville sit-in movement, John Lewis' commitment to change through nonviolence is stronger than ever ? but as he and his fellow Freedom Riders board a bus into the vicious heart of the deep south, they will be tested like never before. Faced with beatings, police brutality, imprisonment, arson, and even murder, the movement's young activists place their lives on the line while internal conflicts threaten to tear them apart.But their courage will attract the notice of powerful allies, from Martin Luther King, Jr. to Attorney General Robert F. Kennedy... and once Lewis is elected chairman of the Student Nonviolent Coordinating Committee, this 23-year-old will be thrust into the national spotlight, becoming one of the "Big Six" leaders of the civil rights movement and a central figure in the landmark 1963 March on Washington for Jobs and Freedom.
Title from eBook information screen..
Requires OverDrive Read (file size: N/A KB) or Adobe Digital Editions (file size: 194232 KB) or Kobo app or compatible Kobo device (file size: N/A KB) or Amazon Kindle (file size: N/A KB).
Keywords: Young Adult Nonfiction; African American Nonfiction; Comic and Graphic Books; History; Electronic books